Pengaruh Vessel Leadership Training Terhadap Key Performance Indicator (KPI) Kapal di PT. Pelayaran Nasional Ekalya Purnamasari Tbk - Dyah Pasha Pradhani, Novia; Dwi Retnandari, Septina; Retian Asfirah, Lia (Jurnal Maritim Polimarin, 2024)
Effective human resource management is the main key to achieving optimal company performance. PT. Pelayaran Nasional Ekalya Purnamasari Tbk has implemented the Vessel Leadership Training program as one of the strategic initiatives to improve the ship's Key Performance Indicators (KPIs). The research started from a problem in the form of low KPIs that proved the low service to customers. This aims to examine the influence of leadership training on ship KPIs at PT. This study uses a quantitative method with 45 respondents consisting of the top three crew members (Master, Chief Engineer, and Chief Officer) who have participated in the training program. Data were collected through questionnaires and data analysis was carried out with a simple linear regression test to measure the influence between independent variables and dependent variables. The results of the study show that Vessel Leadership Training has a positive and significant influence on ship KPIs. The training has been proven to improve the operational performance of ships in terms of timeliness, shipping safety, regulatory compliance, and smooth operations. The suggestion for further research is to further examine other factors that may affect the effectiveness of leadership training, as well as evaluate the long-term impact of such training on ship performance.